Banking And Finance In Islamic Law Perspective - Yusmalinda Yusmalinda (Proceeding International Seminar of Islamic Studies, 2019)
This study describes how the role of Islamic banking and finance in Indonesia and examined in the perspective of Islamic law. As it is known that since the 20th century in the Islamic world there was a discourse about the need for interest-free Islamic banks, to serve the needs of Muslims who are not pleased with the application of interest in banking because it is included in usury, namely transactions that are prohibited by Islamic law. In Indonesia, the transformation of conventional banking towards sharia banking began in 1991, beginning with PT. Bank Muamalat Indonesia Tbk, as the first commercial bank in Indonesia to operate based on Islamic law which has been recognized by Law No 10 of 1998 concerning Amendment to Law Number 7 of 1992 concerning Banking. This study uses a descriptive analytical approach and using library research that is used is descriptive analysis. Based on this research, it can be concluded that conventional banking is forbidden by jumhur ulama because it contains usury. In Indonesia, Islamic Banking has been operating in accordance with Islamic law and has been legalized by the MUI.